Prototipe Automatic Filling Machine Using PLC CP2E - Maulidia Ika Safitri; Rahman Arifuddin; Subairi Subairi (Muhammadiyah University, Sidoarjo, 2026)
The manual liquid filling process still has several disadvantages, such as inconsistencies in filling volumes, low work efficiency, and high likelihood of operator errors. This research aims to design and implement an Automatic Filling Machine based on PLC Omron CP2E by utilizing a flow sensor as a volume measurement feedback and a servo motor as an actuator to regulate the opening of the ball valve. The system works by calculating the amount of pulses produced by the flow sensor using the High Speed Counter feature on the PLC to determine the volume of liquid that has flowed. The Proportional control (P-Only) method is applied to adjust the position of the servo based on the error value between the target volume and the actual volume so that the valve closing process is carried out gradually. The test results showed that the system was able to achieve a target volume of 250 mL with an average actual volume of 250 mL, an average error of 0%, and an average charging time of 32.57 seconds. The optimal Kp value of 0.168 results in an actual volume that corresponds to the target so that it is chosen as the best control parameter. Based on these results, the system designed is able to automatically fill liquids with a good level of accuracy, stability, and consistency.